EDUCATIONAL POLICY AND TRENDS OF THE HIGHER SCHOOL IN THE CIS - O. A. Nesterchuk (Проблемы постсоветского пространства)
In article contradictions of system of the higher education of the CIS are noted. Groups of trends of the higher school of the Commonwealth countries as results of educational policy and adaptation of higher education institutions to modern conditions are allocated and considered.